Towards a Character Language : Rethinking the Nature of Human Language in Indonesian Context - . Jumanto (Serat Acitya, 2012)
This paper is about a character language, i.e. a language with character through pragmatic viewpoints. A character  language should be directed, the writer argues, to politeness (distant language) and camaraderie (close language), the two varieties of language use in every diglossic speech situation. The writer’s arguments are, among others, that distant language is formal, indirect, and non-literal, and that close language is informal, direct, and literal. Distant language is spoken to hearers with power factor, while close language is spoken to hearers with solidarity factor. Ignorance or incompetence of this may cause impoliteness, i.e. rude situations or awkward situations in interpersonal interactions. This tendency elaborates pragmatic viewpoints (Goffman’s  positive and negative face, 1959; Brown and Levinson’s positive and negative politeness strategies, 1987; Renkema’s solidarity and respect politeness, 1993; and Jumanto’s politeness and friendship, 2008; 2011) and types of hearer elaborated by Brown and Gilman (1968) and advocated by Jumanto (2011). Examples in the Indonesian language are given to support the everyday-use-of-Indonesian-language arguments.   Key Words:    character, language, pragmatics, meaning, verbal interaction, social distance, politeness, object language, metalanguage, character language